PS 13-10 INDUCTION OF ANGIOGENESIS BY A TYPE III PHOSPHODIESTERASE INHIBITOR THROUGH ACTIVATION OF PPAR GAMMA AND cAMP PATHWAYS. (September 2016) - SANADA, FUMIHIRO; Taniyama, Yoshiaki; Ikeda-iwabu, Yuka; Otsu, Rei; Muratsu, Jun; Rakugi, Hiromi; Morishita, Ryuichi
Abstract : Objective: Peripheral arterial disease (PAD) is highly prevalent in the elderly as well as in the subjects with cardiovascular risk factors such as diabetes. Approximately 2–4% of those affected with PAD commonly complain of intermittent claudication (IC). Cilostazol, a type III phosphodiesterase inhibitor, is the only FDA-approved drug for the treatment of IC. Cilostazol has been shown to be beneficial for the improvement of pain-free walking distance in patients with IC in a series of randomized clinical trials. However, the underlying mechanism how cilostazol improved IC symptoms is still unclear. Design and Method: In this study, the effect of cilostazol on ischemic leg was investigated in mouse ischemic hind limb model. Results: Administration of cilostazol significantly increased the expression of hepatocyte growth factor (HGF), vascular endothelial growth factor, angiopoietin-1, and peroxisome proliferator-activated receptor (PPAR)-γ in vasculature. The capillary density in ischemic leg was also significantly increased in cilostazol treatment group as compared to control and aspirin treatment group. However, an increase in capillary density and the expression of growth factors was almost completely abolished by co-administration of HGF-neutralizing antibody, suggesting that cilostazol enhanced angiogenesis mainly through HGF. In vitro experiment revealed that cilostazol treatment increased HGF production in vascular smooth muscle cells via two major pathways, PPAR-γ and cAMP pathways. Conclusions: Our data suggest that the favorable effects of cilostazol on ischemic leg might be through the angiogenesis through the induction of HGF via PPAR-γ and cAMP pathways.